1991
DOI: 10.1007/bf00215860
|View full text |Cite
|
Sign up to set email alerts
|

On the coordination of motor output during visual flight control of flies

Abstract: Summary. In tethered flying houseflies (Musca domestica), the yaw torque produced by the wings is accompanied by postural changes of the abdomen and hindlegs. In free flight, these body movements would jointly lead to turning manoeuvres of the animal. By recording the yaw torque together with the lateral deflections of either the abdomen or the hindlegs, it is shown that these motor output systems act in a highly synergistic way during two types of visual orientation behavior, compensatory optomotor turning re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
6
19
0
Order By: Relevance
“…During most flight bouts the head motion in flight generally consists of small, rapid movements, as well as large head motions that typically accompany large turns. As expected from prior studies (Hengstenberg, 1991a;Zanker et al, 1991;van Hateren and Schilstra, 1999), we observed a strong coordination between head yaw and wing motion, i.e. the head turned in the same direction of an intended turn.…”
Section: What Does the Discrepancy Between Head-fixed And Head-free Rsupporting
confidence: 90%
“…During most flight bouts the head motion in flight generally consists of small, rapid movements, as well as large head motions that typically accompany large turns. As expected from prior studies (Hengstenberg, 1991a;Zanker et al, 1991;van Hateren and Schilstra, 1999), we observed a strong coordination between head yaw and wing motion, i.e. the head turned in the same direction of an intended turn.…”
Section: What Does the Discrepancy Between Head-fixed And Head-free Rsupporting
confidence: 90%
“…Previous studies on flight control in tethered flies suggest that hind leg steering during optomotor yaw response reinforces wingflapping-induced moments by strongly increasing (decreasing) the leg extension angle on the inner (outer) side of an intended yaw turn (Zanker, 1988a(Zanker, , 1991. The author proposed that this synergy increases the fly's agility and manoeuvrability, which may, in turn, increase survival rate during aerial predation by dragonflies (Combes et al, 2012).…”
Section: Coherence Of Steeringmentioning
confidence: 98%
“…The vast majority of previous studies on the significance of body appendages for force and moment support in actively flying animals were conducted in insects such as the small fruit fly (Götz et al, 1979;Zanker, 1988b), the house fly (Zanker et al, 1991), orchid bees (Combes and Dudley, 2009) and moths (Cheng et al, 2011;Hedrick and Daniel, 2006). Early studies on various freely flying insect species suggested that leg steering and shifting the insect's centre of body mass support wing-induced moments during manoeuvring (Ellington, 1984d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, it is necessary to exclude the possibility that the relatively slow dynamics of the behaviourally generated motion traces is the consequence of the lowpass properties of the flight simulator . Since in another behavioural context (object detection and fixation), that was also analysed using the flight simulator, much faster responses are generated by the fly than during optomotor course control (Egelhaaf 1987;Zanker et al 1991;Kimmerle et al 1997), the dynamics of the flight simulator are not the main determinant of the dynamics of the behaviourally generated optomotor responses. In addition, increasing or decreasing the cut-off frequency of the lowpass filter in Encoding Visual Motion in Real-Time 265 the flight simulator by a factor of two does not change the dynamics of the optomotor responses in any obvious manner .…”
mentioning
confidence: 99%